The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1037/spy0000051
|View full text |Cite
|
Sign up to set email alerts
|

The role of performance feedback on the self-efficacy–performance relationship.

Abstract: We report 3 studies that explore the moderating role of performance feedback on the within-person relationship between self-efficacy and performance. In Study 1, we provided participants with either very little feedback (current trial performance) or a wider range of previous performance markers (baseline performance and current trial performance) before making efficacy judgments. In Study 2, we refined the selfefficacy measure by providing participants with more detailed feedback regarding their past performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 35 publications
3
33
1
4
Order By: Relevance
“…However, previous experimental research has indicated positive effects of self-efficacy on both exploration and exploitation [53], which is similar to the association between grit and exploration found by Dale et al [17]. In support, self-efficacy was associated with better performance in studies [33], sport [34], work [35,59], and health-promoting behaviors involving dietary habits and exercise [36], medication adherence [60], and patients' mental and physical health [61]. Self-efficacy has been reported to be significantly and positively correlated with GMV in the left posterior insular cortex [62] and the posterior precuneus [63].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, previous experimental research has indicated positive effects of self-efficacy on both exploration and exploitation [53], which is similar to the association between grit and exploration found by Dale et al [17]. In support, self-efficacy was associated with better performance in studies [33], sport [34], work [35,59], and health-promoting behaviors involving dietary habits and exercise [36], medication adherence [60], and patients' mental and physical health [61]. Self-efficacy has been reported to be significantly and positively correlated with GMV in the left posterior insular cortex [62] and the posterior precuneus [63].…”
Section: Discussionsupporting
confidence: 71%
“…These scales are valuable because they are designed to evaluate positive thinking but do not include the meanings of exploration or exploitation, which in this sense makes a good contrast with two other variables of ambidexterity. Self-efficacy, the confidence in one's ability to achieve a desired outcome [32], has been found to be associated with better performance in studies [33], sport [34], work [35], and health-promoting behaviors related to diet and exercise [36]. Self-esteem-an individual's subjective view of his or her own value, which involves a variety of beliefs about the self-is associated with satisfaction with one's life and job, fewer interpersonal problems, and fewer psychological problems such as anxiety and depression [37].…”
Section: Introductionmentioning
confidence: 99%
“…Selon Bandura (1997Bandura ( /2003, il existe une relation réciproque entre le sentiment de compétence et la performance, et normalement, cette relation s'avère positive, ce qui est confirmé par un grand éventail d'études (Moritz, Feltz, Fahrbach et Mack, 2000). Les sujets qui réussissent le mieux s'autoévaluent comme étant plus efficaces (sentiment de compétence) et, par conséquent, s'engagent dans des tâches plus difficiles en obtenant des performances plus élevées (Beattie, Woodman, Fakehy et Dempsey, 2016). Les travaux les plus récents examinant le lien entre le sentiment de compétence et les performances avec des modèles autorégressifs croisés montrent que l'influence des performances passées sur le sentiment de compétence est plus forte que l'inverse (Sitzmann et Yeo, 2013;Talsma, Schüz, Schwarzer et Norris, 2018).…”
Section: Le Sentiment De Compétenceunclassified
“…D'où l'importance d'avoir une rétroaction appropriée dans les différentes étapes d'une expérience ou d'une tâche quelconque. Dans leur première étude, Beattie et al (2016) ont constaté qu'une rétroaction limitée conduisait à une relation négative (même si non significative) entre sentiment de compétence et performance, tandis qu'une rétroaction plus consistante amenait à un résultat positif et statistiquement significatif.…”
Section: Le Sentiment De Compétenceunclassified
See 1 more Smart Citation